Influence of Holding Time and Quenching on the Hardness of Carbon Steel in Pack Carburizing Process with Mangrove Charcoal Media - Gusrianti, Gusrianti; Indra, Akmal; Fajrul, Rahmat (Universitas Negeri Padang, 2024)
The demand for metal materials in the industry is currently on the rise. However, existing metal materials often fail to meet the desired properties and characteristics. One such material is carbon steel, which is extensively utilized across various industrial sectors, particularly in small and medium-scale industries as a construction material. This study aims to investigate the impact of holding time and quenching variations on the pack carburizing process, as well as to determine the hardness value of carbon steel before and after undergoing pack carburizing. Experimental research was conducted using Rockwell hardness testing on 16 specimens, with 5 points tested on each specimen. The specimens were subjected to pack carburizing using mangrove wood charcoal at a temperature of 900°C, with holding time variations of 30 minutes, 60 minutes, 90 minutes, and 120 minutes. Different cooling media were utilized, including seawater, rainwater, well water, and mineral water. The results revealed that specimens treated with a holding time of 120 minutes and quenched with seawater exhibited the highest hardness of 83.94 HRA. Prior to the pack carburizing process, the hardness was 47.54 HRA, which increased to a range of 60.72 HRA to 83.94 HRA after the process.